Linkage of neutrophil serine proteases and decreased surfactant protein-A (SP-A) levels in inflammatory lung disease. Issue 4 (26th March 2004) - Rubio, F; Cooley, J; Accurso, F J; Remold-O'Donnell, E
Abstract : Background: In patients with cystic fibrosis (CF) neutrophils are recruited in excess to the airways yet pathogens are not cleared and the patients suffer from chronic infections. Recent studies have shown a deficiency in airway fluids from patients with CF and other inflammatory pulmonary conditions of surfactant protein A (SP-A), a pattern recognition molecule that facilitates uptake of microbes by macrophages and neutrophils. Methods: In vitro simulations were used to test the hypothesis that decreased SP-A levels in CF might be the result of degradation by neutrophil serine proteases. Results: Very low levels of the neutrophil granule serine proteases cathepsin G, elastase, and proteinase-3 rapidly degraded pure SP-A when tested in buffered saline. The order of potency was cathepsin G>elastase>proteinase-3. The addition of cathepsin G or elastase to normal bronchoalveolar lavage (BAL) fluid caused a dose dependent degradation of endogenous native SP-A. Cathepsin G and elastase were present in the BAL fluid from many patients with CF. Simple incubation of protease positive BAL fluid from patients with CF caused a time dependent degradation of added SP-A or, where present, endogenous SP-A. The degradation of SP-A by protease(s) in BAL fluid of patients with CF was abrogated by diisopropylfluorophosphate and monocyte/neutrophil elastase inhibitor. Conclusions: The findings strongly suggest that the neutrophil serine proteases cathepsin G and/or elastase and/or proteinase-3 contribute to degradation of SP-A and thereby diminish innate pulmonary antimicrobial defence.